Relationship between financial inclusion, inflation and financial stability of countries around the world and lessons for Vietnam - Pham, Tien Dat; Tran, Thi Kim Oanh (Journal of Finance - Marketing Research, 2024)
The study examines the correlation between financial inclusion, inflation, and financial stability across 58 countries during the period 2004-2022, employing PVAR analysis. Impulse-response function outcomes indicate a negative relationship between financial stability and both financial inclusion and inflation rate, while financial inclusion and inflation rate display a positive correlation. These results suggest that financial inclusion may exacerbate financial instability, potentially leading to prolonged inflation. Additionally, variance decomposition results affirm the interconnectedness of financial inclusion, inflation, and financial stability. Based on these findings, we offer policy suggestions for enhancing financial stability in Vietnam.